The Pengaruh Pendidikan Sebaya Terhadap Perilaku Pencegahan Demam Berdarah Dengue (DBD) Pada Santri Madrasah Aliyah Dayah Modern Ihyaaussunnah Kota Lhokseumawe - Nazirah, Jihan; Sofia, Rizka; Utariningsih, Whenny (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
Diabetes mellitus as known as DM, is a serious chronic disease which happens due to pancreas unable to produce insulin enough, or when the body cannot use the insulin that it already produces effectively. Patients with the diagnosis of DM need long term treatment / therapy in order to reduce the complication accident. If the diabetes is not handled well, it causes complications which are threatening and endanger life. Acute complications are being significant contributors towards death, loss of costs, and bad life quality. This research study aims to know the determinants of life quality of patients with diabetes mellitus at Banda Sakti public center, Lhokseumawe city. This research using a non-experimental method with prospective approach and analyzed with descriptively correlation. This research study adapts a cross section design. Amount of samples are 98 individuals which are determined based on the Slovin formula. The sampling is using a sequential random sampling method. There are three variables involed in this study, which are the life quality of patients with DM as a dependent variable. And duration variables experiencing DM and blood sugar level as independent variables. The analysis data method is using a univariate and bivariate (chi-square test) analysis method. The analysis results show that patients with Diabetes Mellitus (DM) type 2 at Banda Sakti Public health center Lhokseumawe are dominated by female patients (58,2%), mostly suffering in the age group of 40-60 years old (70,4%). With a long period of time above 10 years (49%). Patients with diabetes mellitus at banda sakti public health center have rough blood sugar that is not under control (59,2%) and most patients have bad life quality equals to 56,1%. The duration of DM and blood sugar level is related to life quality of patience with DM type 2 at banda sakti public health center, Lhokseumawe.